Trade credit and cross-country predictable firm returns - Albuquerque, Rui; Ramadorai, Tarun; Watugala, Sumudu W. (Journal of Financial Economics, 2015)
We investigate the role of trade credit links in generating cross-border return predictability between international firms. Using data from 43 countries from 1993 to 2009, we find that firms with high trade credit located in producer countries have stock returns that are strongly predictable based on the returns of their associated customer countries. This behavior is especially prevalent among firms with high levels of foreign sales. To better understand this effect we develop an asset pricing model in which firms in different countries are connected by trade credit links. The model offers further predictions about this phenomenon, including stronger predictability during periods of high credit constraints and low uninformed trading volume. We find supportive empirical evidence for these predictions.